Achieving self-sustainability of service delivery in an eye care program in Madagascar using time-driven activity based costing - Philippe Rakotondrajoa; Tantely Rakotomamonjy; Randrianaivo Jean Baptiste; Lisa Demers; Peter Kileo; Michele Anholt; Jaafar Aghajanian; Ken Bassett (BMC, 2020)
Abstract Background In the absence of adequate and reliable external funding, eye care programs in developing countries need a high level of financial self-sustainability for maintenance and growth. To cope with these cost pressures, an eye care program in Sava, Madagascar adopted a Time-Driven Activity Based Costing (TDABC) methodology to better manage the cost of, and to improve revenue associated with, their three principle activities: consultation visits, cataract operations, and sale of glasses. Methods Direct (variable) and indirect (fixed) cost estimates and revenue sources were gathered by activity (consultation, cataract operation, sale of glasses) and location (hospital or outreach) and TDABC models were established. Estimates were made of the proportion of the ophthalmologist's time (by far the scarcest and most expensive resource) dedicated to consultation, cataract operation, or sale of glasses. These proportions were used to attribute costs by activity. The hospital manager and medical director modified staff roles, program activities, and infrastructure investments to reduce costs and expand revenue sources by activity while monitoring activity specific efficiency and profit. Results The TDABC model for patient consultations showed that they were time consuming for the ophthalmologist and only resulted in net profit for the institution if the ophthalmologist converted most cataract patients into accepting surgery and refractive error patients into purchasing glasses from the hospital optical shop. The TDABC model for cataract surgery showed the programs needed to reduce the cost of imported consumable surgical products, reduce operation time, and, most importantly, reduce the number of very costly surgical camps providing essentially free surgery. In addition the model pushed the hospital to train staff in marketing skills so that a higher proportion of cataract cases come directly to the hospital willing to pay for surgery. The TDABC model provided the optical shop manager, for the first time, data on both the cost of supplies (frames and lenses) and the price of glasses sold resulting in strategies to maximize profit through preferential product presentation and customer experience. The eye program in the Sava region in northern Madagascar improved its cost recovery from 68 to 102% through patient revenue. Conclusions TDABC models helped the Sava eye care program develop more efficient service delivery and increase revenue in excess of steadily increasing costs.